Individual and Environmental Factors Shaping Homework Behavior: A Three‐Level Investigation With Hierarchical Linear Modeling - Avcı, Süleyman; Özgenel, Mustafa; Avcu, Akif (Psychology in the schools, 2025)
ABSTRACT This study employed a multilevel, three‐stage hierarchical linear modeling (HLM) approach to examine the factors influencing homework completion, time, and effort behaviors among middle and high school students. The student‐level analysis encompassed a range of variables, including academic achievement, parental education, book ownership, age, homework motivation, emotions, parental involvement, personality, and attitudes. The class‐level analysis incorporated homework quality, feedback quality, autonomy support, and homework frequency, representing teacher involvement. The school‐level analysis included factors that reflected school‐level differences and involved both middle and high school students. The study's findings indicated that homework completion and effort are predominantly influenced by individual‐level factors, while homework time is significantly impacted by class‐level variables. The study underscores the significance of academic achievement, homework motivation, and parental involvement in predicting homework completion and effort. Conversely, teacher feedback quality and autonomy support emerged as important factors affecting homework time and completion rates. This complex model offers a detailed understanding of the details that shape homework behaviors (completion, time, and effort), providing a foundation for designing targeted interventions to enhance student achievement. Summary Student motivation is a primary driver of homework completion and effort, highlighting the importance of engaging and relevant homework assignments to boost motivation. Parental involvement does not significantly predict homework behaviors, indicating that the traditional emphasis on parental roles in homework guidance may need reassessment. Teachers' feedback, while influential, should avoid being overly controlling as it negatively affects all aspects of homework behaviors—completion, effort, and time—underscoring the importance of nonpressuring feedback approaches.